Epidemiology of HTLV-1 Infection and ATL in Japan: An Update - Iwanaga, Masako (Frontiers in Microbiology, 2020)
Adult T-cell leukemia-lymphoma (ATL) is an aggressive T-cell malignancy caused by human T-cell leukemia virus type 1 (HTLV-1) infection that often occurs in HTLV-1-endemic areas, such as Japan, the Caribbean islands, Central and South America, Intertropical Africa, and the Middle East. In Japan, the nationwide estimation of the number of HTLV-1 carriers was at least 1.08 million in 2006–2007. Furthermore, in 2016, the nationwide annual incidence of newly infected with HTLV-1 was first estimated to be 3.8 per 100,000 person-years based on the age-specific seroconversion rates of blood donors in almost all areas of Japan. The incidence rate was three times higher in women than in men, and it was estimated that at least 4,000 new HTLV-1 infections occur yearly among adolescents and adults in Japan. As well known that HTLV-1 infection alone is not a sufficient condition for ATL to develop. To date, a variety of molecular abnormalities and host susceptibilities have been reported as candidate progression factors for the development of ATL in HTLV-1-carriers. In particular, quite recently in Japan, a variety of immunosuppressive conditions have been recognized as the most important host susceptibilities associated with the development of ATL from HTLV-1-carrier status. Furthermore, in 2013–2016 in Japan, a new nationwide epidemiological study of ATL was conducted targeting patients newly diagnosed with ATL in 2010–2011, from which the most current knowledge about the epidemiological characteristics of Japanese patients with ATL was updated as follows: (1) continuing regional unevenness of the distribution of people with HTLV-1, (2) further aging, with the mean age at diagnosis being 67.5 years, (3) declining M/F ratio, (4) increase of the lymphoma subtype, (5) sex differences in subtype distribution, (6) age differences in subtype distribution, and (7) comorbidity condition. In particular, 32.2% of ATL patients had comorbid malignancies other than ATL. However, the number of deaths due to ATL in Japan has been relatively stable, at around 1,000 patients annually, without significant decline from 1999 to 2017. Because the current epidemiological evidence about HTLV-1 and ATL is insufficient, further epidemiological studies are required.